2017
DOI: 10.1002/jsfa.8201
|View full text |Cite
|
Sign up to set email alerts
|

Increased protein content of chickpea (Cicer arietinum L.) inoculated with arbuscular mycorrhizal fungi and nitrogen‐fixing bacteria under water deficit conditions

Abstract: Inoculation with N-fixing bacteria and AM fungi has the potential to benefit agricultural production of chickpea under water deficit conditions and to contribute to increased grain protein content. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 48 publications
3
29
1
2
Order By: Relevance
“…The enhancement of K under moderate water deficit might be one of the factors responsible for improving cowpea tolerance to the stress and positively influencing seed yield, when comparing to the reaming treatments under the same water regime. The ability of PGPR to increase plant biomass, yield and protein content both under greenhouse and field conditions was shown before in legumes (Oliveira et al., ,b; Sindhu, Dua, Verma, & Khandelwal, ). Many studies with various crops showed a positive relationship between PGPR inoculation and drought tolerance (Figueiredo, Burity, Martínez, & Chanway, ; Gusain et al., ; Kohler, Hernández, Caravaca, & Roldán, ; Naseem & Bano, ).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The enhancement of K under moderate water deficit might be one of the factors responsible for improving cowpea tolerance to the stress and positively influencing seed yield, when comparing to the reaming treatments under the same water regime. The ability of PGPR to increase plant biomass, yield and protein content both under greenhouse and field conditions was shown before in legumes (Oliveira et al., ,b; Sindhu, Dua, Verma, & Khandelwal, ). Many studies with various crops showed a positive relationship between PGPR inoculation and drought tolerance (Figueiredo, Burity, Martínez, & Chanway, ; Gusain et al., ; Kohler, Hernández, Caravaca, & Roldán, ; Naseem & Bano, ).…”
Section: Discussionmentioning
confidence: 52%
“…Legume crops are able to establish symbiotic interactions with microbes (e.g. PGPR and AM fungi), which help them cope with unfavourable environmental conditions such as drought (Oliveira et al., ,b; Zahran, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio-inoculations are a relatively simple but effective means to increase crop productivity through the amendment of certain microorganisms. Seed coating of grain legumes has been especially successful for N-fixing bacteria and mycorrhizal fungi (O'Callaghan, 2016;Oliveira et al, 2017;Patil & Alagawadi, 2010). A yield increase of 52% was obtained through coinoculation of chickpea with an N-fixing (Mesorhizobium ciceri) and a P-solubilizing (Pseudomonas jessenii) bacteria (Valverde et al, 2006).…”
Section: Increased Crop Productivity With Microbial Amendmentsmentioning
confidence: 99%
“…Since the future competitiveness of the grain legumes value chain in Europe will depend on agronomic and scientific developments, for this In Focus issue of the Journal of the Science of Food and Agriculture we gathered relevant papers covering novel research addressed by the multidisciplinary teams of the EUROLEGUME project, with the aim of bringing added value to the grain legume chain.…”
mentioning
confidence: 99%